(untitled) (Research, Society and Development, 2022)
Nurses work long hours, face great dilemmas and ambiguous feelings on a daily basis, which in itself generate stresses that, depending on the individuals, can evolve into states that interfere with their well-being, an interference demonstrated in the study when asked about the impact of Covid-19 pandemic at work; 24 (77.42%) said they felt a great impact, 6 (19.35%) said they felt an intermediate impact and 1 (3.23%) said they had little impact; thus, the data show that the Covid-19 pandemic was an aggravating factor in the addition of stressors that facilitate the development of Burnout syndrome. The study aims to understand which factors favor the development of Burnout syndrome in nursing professionals. The present study is an exploratory and descriptive research, with quali-quantitative analysis, with the population of nursing professionals from the eight Basic Health Units, in the city of Guaraí-TO.